2010
DOI: 10.4049/jimmunol.0902336
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Specific Gene Expression in Langerhans Cell Histiocytosis Lesions Reveals a Distinct Profile Compared with Epidermal Langerhans Cells

Abstract: Langerhans-cell histiocytosis (LCH) is a rare disease characterized by heterogeneous lesions containing CD207+ Langerhans cells and lymphocytes that can arise in almost any tissue and cause significant morbidity and mortality. After decades of research, the cause of LCH remains speculative. A prevailing model suggests that LCH arises from malignant transformation and metastasis of epidermal Langerhans cells. In this study, CD207+ cells and CD3+ T cells were isolated from LCH lesions to determine cell-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
275
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(301 citation statements)
references
References 76 publications
(91 reference statements)
15
275
0
11
Order By: Relevance
“…Recent studies have shown that LCH might be malignant in certain cases. Firstly, it was observed that the original cells affected by LCH might arise from early myeloid precursors rather than mature Langerhans cells (9,12). Secondly and of note, our study (China) along with studies by Badalian-Very et al (8) (USA), Satoh et al (10) (France) and Sahm et al (9) (Germany and Austria) identified the BRAF V600E mutation in 31-57% of LCH cases.…”
Section: Discussionsupporting
confidence: 62%
“…Recent studies have shown that LCH might be malignant in certain cases. Firstly, it was observed that the original cells affected by LCH might arise from early myeloid precursors rather than mature Langerhans cells (9,12). Secondly and of note, our study (China) along with studies by Badalian-Very et al (8) (USA), Satoh et al (10) (France) and Sahm et al (9) (Germany and Austria) identified the BRAF V600E mutation in 31-57% of LCH cases.…”
Section: Discussionsupporting
confidence: 62%
“…It will be interesting to postulate that this induced inflammatory infiltrate may further develop into a neoplastic transformation into LCH (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, la expresión genética del CD207+ (langerina) de los histiocitos en las lesiones óseas en comparación con las cé-lulas de Langerhans de la piel demuestra que son dos tipos celulares diferentes 4 . Las células patoló-gicas en la HCL son más probablemente derivadas de las células mieloides dendríticas circulantes que expresan los mismos marcadores (CD1a y CD207) que las células de Langerhans de la piel, pero que además expresan CD14 a diferencia de esta última.…”
Section: Reporte De Casounclassified